Altered CD8(+) T cell immunodominance after vaccinia virus infection and the naïve repertoire in inbred and F(1) mice - Flesch, Inge E.A. (2009)
Previous studies of CD8(+) T cell immunodominance after primary virus infection of F(1) mice compared with their inbred parents have generally concluded that no dramatic changes occur. Here we re-visit this issue using vaccinia virus (VACV), which has a large genome, a recently defined immunodominance hierarchy in mice and is a candidate vector for vaccines. We found that immunogenicity of VACV peptides defined using inbred mice was highly variable in F(1) progeny: some peptides were equally immunogenic in F(1) and inbred, while others elicited responses that were reduced by more than 90% in F(1) mice. Further, the dominance of a peptide in the relevant inbred parent did not predict whether or not it would be poorly immunogenic in F(1) mice. This result held using F(1) hybrids of MHC-congenic mice, suggesting that MHC differences alone were responsible. It was also extended to foreign epitopes expressed by a recombinant VACV vaccine. F(1) mice were less able to mount responses to the poorly immunogenic peptides when used as a sole immunogen, ruling out immunodomination. In addition, conserved TCR Vβ usage between inbred and F(1) mice did not always correlate with strong responses in F(1) mice. However direct estimation of naïve precursor numbers showed that these were reduced in F(1) compared with inbred mice for specificities that were poorly immunogenic in the hybrids. These data have implications for our understanding of the extent to which MHC diversity alters the range of epitopes that are immunogenic in outbred populations.